A grey box model of glucose fermentation and syntrophic oxidation in microbial fuel cells. (January 2016) - de los Ángeles Fernandez, Maria; de los Ángeles Sanromán, Maria; Marks, Stanislaw; Makinia, Jacek; Gonzalez del Campo, Araceli; Rodrigo, Manuel; Fernandez, Francisco Jesus
Highlights: Glucose fermentation and syntrophic oxidation in microbial fuel cells were modeled. Fermentation processes were similar under open and closed circuit operation. The main fermentation product was ethanol. Most of the electricity generated, 90%, came from ethanol oxidation. Glucose oxidation only account for a 10% of the electricity production. Abstract: In this work, the fermentative and oxidative processes taking place in a microbial fuel cell (MFC) fed with glucose were studied and modeled. The model accounting for the bioelectrochemical processes was based on ordinary, Monod-type differential equations. The model parameters were estimated using experimental results obtained from three H-type MFCs operated at open or closed circuits and fed with glucose or ethanol. The experimental results demonstrate that similar fermentation processes were carried out under open and closed circuit operation, with the most important fermentation products being ethanol (with a yield of 1.81 mol mol −1 glucose) and lactic acid (with a yield of 1.36 mol mol −1 glucose). A peak in the electricity generation was obtained when glucose and fermentation products coexisted in the liquid bulk. However, almost 90% of the electricity produced came from the oxidation of ethanol.